Computer and Information Science 2010 - Lee, Roger. (Studies in Computational Intelligence, 2010)
The purpose of the 9th IEEE/ACIS International Conference on Computer and Information Science (ICIS 2010) was held on August 18-20, 2010 in Kaminoyama, Japan is to bring together scientist, engineers, computer users, students to share their experiences and exchange new ideas, and research results about all aspects (theory, applications and tools) of computer and information science, and to discuss the practical challenges encountered along the way and the solutions adopted to solve them The conference organizers selected the best 18 papers from those papers accepted for presentation at the conference in order to publish them in this volume. The papers were chosen based on review scores submitted by members of the program committee, and underwent further rigorous rounds of review.